Peritumoral Edema Is Associated With Postoperative Hemorrhage and Reoperation Following Vestibular Schwannoma Surgery - Guo, Xiaoming; Zhu, Yueli; Wang, Xiaoyu; Xu, Ke; Hong, Yuan (Frontiers in Oncology, 2021)
Background: Postoperative hemorrhage (POH) is a severe complication following vestibular schwannoma surgery that may require surgical treatment. The purpose of our study is to identify risk factors associated with POH and reoperation following the resection of vestibular schwannoma. Methods: We retrospectively recruited 452 vestibular schwannoma patients treated with retrosigmoid approach. The primary outcome was POH, and the secondary outcome was reoperation for POH. Clinical and radiographic data were compared by performing univariate analysis and logistic regression analysis. Results: Among the 452 patients, 37 patients (8.2%) presented with POH and14 patients (3.1%) required reoperation within a 30-day hospitalization period. The univariate analysis showed that peritumoral edema, tumor diameter >30 mm, severe postoperative hypertension, and length of hospital stay were associated with POH and reoperation for POH. Logistic regression analysis showed that peritumoral edema (odds ratio [OR] 4.042, 95% confident interval [CI] 1.830 – 8.926, P = 0.001) and tumor diameter > 30 mm (OR 3.192, 95% CI 1.421 – 7.168, P = 0.005) were independent predictive factors for POH. Peritumoral edema (OR 7.071, 95% CI 2.342 – 21.356, P = 0.001) was an independent predictive factor for reoperation by using logistic regression analysis. Further analysis revealed that larger tumor and incomplete tumor resection were both associated with a higher incidence of peritumoral edema. Conclusion: Peritumoral edema and tumor size are independent risk factors for POH following vestibular schwannoma surgery. And larger hematoma occurs more commonly in tumors with peritumoral edema which may require reoperation. Tumor size and extent of tumor resection are associated with peritumoral edema. Close attention should be paid to high-risk patients especially for those who presented with severe postoperative hypertension.